Microbiome interactions and their ecological implications at the Salton Sea - H Freund*; M Maltz*; M Swenson; T Topacio; V Montellano; W Porter; E Aronson (California Agriculture)
Although the Salton Sea was once a thriving destination for humans and wildlife, it has now degraded to the point of ecosystem collapse. Increases in local dust emissions have introduced aeolian (wind-blown) microorganisms that travel, along with contaminants and minerals, into the atmosphere, detrimentally impacting inhabitants of the region. Proliferation of certain microbial groups in regions of the Sea may have a disproportionate impact on local ecological systems. Yet, little is known about how the biogeochemical processes of this drying lakebed influence microbial community composition and dispersal. To elucidate how these microorganisms contribute, and adapt, to the Sea's volatile conditions, we synthesize research on three niche-specific microbiomes — exposed lakebed (playa), the Sea, and aeolian — and highlight modern molecular techniques, such as metagenomics, coupled with physical science methodologies, including transport modeling, to predict how the drying lakebed will affect microbial processes. We argue that an explicit consideration of microbial groups within this system is needed to provide vital information about the distribution and functional roles of ecologically pertinent microbial groups. Such knowledge could help inform regulatory measures aimed at restoring the health of the Sea's human and ecological systems.